Russian Settlement and Development of Middle Irtysh Territories in 17th-19th Centuries - N. A. Sedelnikova (Научный диалог)
This article examines the process of settlement and development of the Middle Irtysh territories. Special attention is given to the northern regions of the Omsk region, characterized by their remoteness and natural-geographical location features. The focus is on the Russian settlers’ colonization of the region. The author highlights the nature and extent of administrative influence by various state authorities on the settlement and development process during the pre-revolutionary period. The author discusses the model of relationships between the Russian population and indigenous inhabitants. It is demonstrated that state policy had a corrective influence on the resettlement and development process. The formation of a settlement network was largely determined by the policy of relocating Russians from less fertile lands of the country’s regions. Favorable geographical and climatic conditions, along with the presence of river arteries, made the Middle Irtysh territory convenient for settlers who established their own settlements or resettled in indigenous villages. The stages of settlement in the Middle Irtysh are identified, and archival data are introduced into scholarly discourse.